AshNet: Facilitating the use of wood ash as a forest soil amendment in Canada - K.D. Hannam; L. Venier; E. Hope; D. McKenney; D. Allen; P.W. Hazlett (The Forestry Chronicle)
The growing demand for bioenergy has raised concerns about the sustainability of intensive forest biomass removal. Less attention has been paid to the ash generated when forest biomass is combusted to produce energy. In Canada, this ash is often landfilled, but in some countries, wood ash is applied to the soil to maintain or improve soil fertility and forest health. AshNet is a network of Canadian scientists, foresters, policy makers and industry representatives that has formed to address opportunities for and challenges to the use of wood ash as a forest soil amendment. To date, AshNet collaborators have produced a guide to navigating the regulatory approval process, and completed a techno-economic analysis of the costs associated with landfilling wood ash versus using it as a forest soil amendment. Practical methods for optimizing ash quality and applying it on forested sites are being investigated. Applications of wood ash are also being examined as a tool for emulating some of the effects of wildfire on soil chemistry. The results of research trials established by AshNet collaborators across Canada will be shared to help develop and refine forest management policies and practices surrounding soil applications of wood ash. Updates on AshNet’s activities are available at (http://cfs.nrcan.gc.ca/projects/140 (English); http://scf.rncan.gc.ca/projets/140?lang=fr_CA (French)).